Exponential-type error probabilities for multiterminal hypothesis testing - Han, T.S.; Kobayashi, K. (IEEE transactions on information theory, 1989)
Multiterminal hypothesis testing is considered, subject to the exponential-type constraint alpha /sub n/<or=exp(-nr) on the error probability of the first kind. The problem is to determine the minimum beta */sub n/ of the error probability of the second kind under the given constraint at limited rates R/sub 1/ and R/sub 2/ for observing the respective pairs of variables. Good lower bounds on the power exponent for beta */sub n/ are presented by invoking basic properties of r-divergent sequences. In particular, the one-bit and the zero-rate compression cases are considered. The power exponent for the former and a lower bound for the latter are established.< >